(untitled) (Salt Lake City, Utah, 1997)
As in previous editions, Life 5/e shows biology not as a collection of facts, but as a dynamic discipline. The student's understanding of biological processes is developed through effective pedagogy, using a smooth narrative, rich experimental contexts and spectacular art, all backed by impeccable scholarship
Keywords: Biology,Sinh học